Internalisasi Nilai-Nilai Tawadhu dalam Pembelajaran Pendidikan Agama Islam dan Implikasinya Sikap Moderat dalam Beragama Studi Kasus SMP N 3 Cepiring Kabupaten Kendal - Irdia Azidar (Attractive : Innovative Education Journal, 2024)
This study aims to: (1) To find out the content of tawadhu' value in pai learning at SMPN 3 Cepiring Kab. Kendal.. (2) To know the internalization process of Tawadhu' value in PAI lessons at SMPN 3 Cepiring Kab. Kendal. (3) . To find out the impact of internalization of tawadhu value in PAI learning on moderation attitude in religion at SMPN 3 Cepiring Kab. Kendal. This type of research uses qualitative research, with the validity of observation data and triangulate data wherein the practice of research is crossed using interview guidelines. Based on the results of research that has been conducted at SMPN 3 Cepiring Kab. Kendal with the title "Internalization of Tawadhu Value' in PAI Learning And Its Implications on Moderate Attitudes in Religion in SMPN 3 Cepiring Kab. Kendal ", Researchers can conclude that Curriculum content that refers to tawadhu' values is expected to be useful as a learning tool to apply tawadhu' attitude in speaking to teachers and others older than him. The content of tawadhu value in the study of Islamic religious education there is already a value tawadhu'. Therefore, the thing that needs to be done by educators or educators involved in it is to apply to students to always respect the father of the teacher, have a manners attitude to friends. And get used to being tawadhu' to everyone older than him.